Genetics of bipolar disorder. Issue 8 (1st August 1999) - Craddock, Nick; Jones, Ian
Abstract : Bipolar disorder (also known as manic depressive illness) is a complex genetic disorder in which the core feature is pathological disturbance in mood (affect) ranging from extreme elation, or mania, to severe depression usually accompanied by disturbances in thinking and behaviour. The lifetime prevalence of 1% is similar in males and females and family, twin, and adoption studies provide robust evidence for a major genetic contribution to risk. There are methodological impediments to precise quantification, but the approximate lifetime risk of bipolar disorder in relatives of a bipolar proband are: monozygotic co-twin 40-70%; first degree relative 5-10%; unrelated person 0.5-1.5%. Occasional families may exist in which a single gene plays the major role in determining susceptibility, but the majority of bipolar disorder involves the interaction of multiple genes (epistasis) or more complex genetic mechanisms (such as dynamic mutation or imprinting). Molecular genetic positional and candidate gene approaches are being used for the genetic dissection of bipolar disorder. No gene has yet been identified but promising findings are emerging. Regions of interest identified in linkage studies include 4p16, 12q23-q24, 16p13, 21q22, and Xq24-q26. Chromosome 18 is also of interest but the findings are confusing with up to three possible regions implicated. To date most candidate gene studies have focused on neurotransmitter systems influenced by medication used in clinical management of the disorder but no robust positive findings have yet emerged. It is, however, almost certain that over the next few years bipolar susceptibility genes will be identified. This will have a major impact on our understanding of disease pathophysiology and will provide important opportunities to investigate the interaction between genetic and environmental factors involved in pathogenesis. This is likely to lead to major improvements in treatment and patient care but will also raise important ethical issues that will need to be addressed.